Perubahan Nilai BA pada Pelvic Organ Prolaps Quantification (POPQ) terhadap Kualitas Berkemih Pre dan Pasca Opreasi Kolporafi Anterior paa Pasien Sistokel - Ramadona, Izwin; Siswishanto, Rukmono; Pangastuti, Nuring (JURNAL KESEHATAN REPRODUKSI, 2017)
Background: Anterior colporrhaphy is used to correct anatomical abnormalities of POP, especially cystocele. In the cystocele, POPQ is focused on Ba point. However, no reference value has been established during evaluation on the changes of Ba’s pre and post operation. A measurement is required to describe the value of Ba in POPQ to the quality of patients’s micturition who have undergone anterior colporrhaphy on cystocele indication.Objective: To determine whether a change of Ba value more than 4 cm post anterior colporrhapy can improve voiding quality.Method: This study used a pretest-posttest design by measuring the value of Ba and voiding quality (UDI6 score) in cystocele patients before and after anterior colporrhapy. Ba value changes compared with changes in postoperative voiding quality.Result and Discussion: There were 20 subjects recruited from January until July 2016 who met the inclusion criteria. There were significant differences between the voiding quality and changes of Ba value before and after surgery for 2nd and 6th week (p<0.001). From the bivariate analysis there were no differences in changes of voiding quality for Ba> 4 cm compared ≤4 cm (p = 0.34; RR 1.43; 95% CI 0.61-3.37). Age, BMI and parity had no significant affects the voiding quality before and after surgery (p= 0.12, p= 0.62, p=0.27). From a logistic regression analysis of variables change in value of Ba and external variables of age, BMI and parity were not statistically significant influence the voiding quality.Conclusion: Changes in the value of Ba more than 4 cm from baseline in patients who undergo anterior colporrhapy does not improve the voiding quality.Keywords: Ba value, voiding quality, anterior colporrhapy.